Failure to breathe at birth: causes and assessment - Roberton, N.R. Clifford (The Turkish Journal of Pediatrics, 1991)
A frequent misconception is that delayed onset of respiration is the result of intrapartum asphyxia. However, many factors other than asphyxia can delay the onset of respiration after delivery. To understand the effect of asphyxia on both the fetus and the neonate, and in particular in delaying the onset of spontaneous respiration, it is convenient to consider chronic partial asphyxia and acute asphyxia separately. In this article, the values of the Apgar score and cord blood pH were also evaluated.